Influence of particle shape on dilatancy and liquefaction susceptibility - Ranjpour, Deniz. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2015., 2015)
Dilatancy is a volumetric parameter directly dependant on void ratio (e), and as a result relative density (ID), as well as con nement pressure p0 i. Besides, liquefaction is a behavior of saturated cohesionless soils under undrained condition, depending on the increase of pore water pressure inside the voids during cyclic loading. The e ect of dilatancy on liquefaction phenomena has been studied by other researchers and in general, they concluded that phases of dilation can result in signi cant regain in shear sti ness and strength, as a result of instances of pore-pressure reduction. The aim of this study is to investigate the in uence of particle shape on peak dilation angle and liquefaction susceptibility. Additionally, the correlation between peak dilatancy angle and liquefaction susceptibility is examined. For this purpose, rst of all, microscopic pictures of 50 individual particles of 3 sand types were processed using an image processing software (ImageJ) to quantify their average circularity and roundness. Then conducting CD triaxial tests on each of 3 sand types, dilatancy constants and m of Cinicioglu and Abadkon [30] relationship were obtained. Finally over 200 cyclic simple shear tests were conducted on sand specimens observe peak dilatancy angle-number of cycles to liquefy relationships for the sand types. De ning normalized number of cycles to liquefy, the relationship between peak dilatancy angle and normalized number of cycles to liquefy was investigated. Other cyclic shearing variables were also taken into account. The e ects of initial cyclic shear stress, consolidation pressure, stress ratio amplitude and cyclic period on dynamic behavior were investigated. The most important point about this study is probing the e ect of di erent agents on dilation angle and liquefaction susceptibility from a more numerical point of view.
Keywords: Particle methods (Numerical analysis)